Associations of Cholesteryl Ester Transfer Protein TaqIB Polymorphism with the Composite Ischemic Cardiovascular Disease Risk and HDL-C Concentrations: A Meta-Analysis - Guo, Shu-xia (Int J Environ Res Public Health, 2016)
Background: Previous studies have evaluated the associations between the cholesteryl ester transfer protein (CETP) TaqIB polymorphism (rs708272), the risk of developing composite ischemic cardiovascular disease (CVD) and the concentration of high-density lipoprotein cholesterol (HDL-C), but results remain controversial. The objective of this study was to investigate whether a relationship exists between these factors. Methods: We conducted a meta-analysis of available studies to clarify the associations of the CETP TaqIB polymorphism with HDL-C concentration and the composite ischemic CVD risk in both Asians and Caucasians. All statistical analyses were done with Stata 12.0. Results: Through utilization of the Cochrane Library, Embase, PubMed, Web of Science, Springer, China Science and Technology Journal Database, China National Knowledge Infrastructure, Google Scholar, and Baidu Library, a total of 45 studies from 44 papers with 20,866 cases and 21,298 controls were combined showing a significant association between the CETP TaqIB variant and composite ischemic CVD risk. Carriers of allele TaqIB-B1 were found to have a higher risk of composite ischemic CVD than non-carriers: OR = 1.15, 95% CI = 1.09–1.21, p < 0.001. Meanwhile, 28 studies with 23,959 subjects were included in the association between the CETP TaqIB polymorphism and the concentration of HDL-C. Results suggested that carriers of the B1B1 genotype had lower concentrations of HDL-C than those of the B2B2 genotype: SMD = 0.50, 95% CI = 0.36–0.65, p < 0.001. Conclusions: The synthesis of available evidence demonstrates that the CETP TaqIB polymorphism protects against composite ischemic CVD risk and is associated with a higher HDL-C concentration in both Asians and Caucasians.